INDONESIA DAN KONSEPSI NEGARA AGRARIS - Lailatusysyukriyah Lailatusysyukriyah Lailatusysyukriyah (Program Studi Pendidikan Sejarah - Universitas Samudra, 2015)
Historiography is a scripted product has been building by the specific value. The value has been discoursing in the teaching of history to each generation. A discourse of agricultural Indonesian state is a doctrine has been building by Dutch colonialism, more rapidly since the era of an economic plantation. The conception had been keeping away Indonesian national character building from the ancestor’s heritage based on maritime. Indonesian has been forgetting the tradition of maritime because of the doctrine of agricultural state. History teaching in Indonesia must change the conception of the agricultural state became the maritime state based on long tradition of historical fact, long time before the colonial era.